2023
DOI: 10.12688/wellcomeopenres.18915.1
|View full text |Cite
|
Sign up to set email alerts
|

Towards achieving transnational research partnership equity: lessons from implementing adaptive platform trials in low- and middle-income countries

Abstract: Background: Use of adaptive clinical trials, particularly adaptive platform trials, has grown exponentially in response to the coronavirus disease (COVID-19) pandemic. Implementation of these trials in low- and middle-income countries (LMICs) has been fostered through the formation or modification of transnational research partnerships, typically between research groups from LMICs and high-income countries (HICs). While these partnerships are important to promote collaboration and overcome the structural and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Funding such major networks inevitably involves opportunity costs—for other kinds of research, and for research institutions not involved in those networks. Here, and in the five WHO-commissioned reviews,2 9–12 we draw attention to how all parts of the research ecosystem need to keep in view these key ethical questions of power, equity and respect for local contexts and needs, as they take forward these effective models of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Funding such major networks inevitably involves opportunity costs—for other kinds of research, and for research institutions not involved in those networks. Here, and in the five WHO-commissioned reviews,2 9–12 we draw attention to how all parts of the research ecosystem need to keep in view these key ethical questions of power, equity and respect for local contexts and needs, as they take forward these effective models of research.…”
Section: Discussionmentioning
confidence: 99%
“…The success of adaptive platform trial designs in responding to COVID-19, and the endorsement by the WHA of major clinical trial networks, highlights the need to review experience to date so that trials can be conducted even quicker and better in future emergencies: driven by scientific rigour, and underpinned by sound ethical practice. Drawing on five reviews commissioned by the WHO Health Ethics and Governance Unit,2 9–12 that subsequently formed the basis for an expert round table held in Geneva in July 2022, we offer the following ethics-related key considerations to support the further development of international collaborative adaptive platform trials. Priority questions for future research and practice identified at the round table are set out in box 1.…”
Section: Looking To the Futurementioning
confidence: 99%
“…Modlin et al have defined the eight dimensions of equity in global health partnerships specific to clinical trials. 40 These are: epistemic structures, funding, ethics oversight, regulatory oversight, post-trial access, knowledge translation and research capacity strengthening and maintenance. The challenge is how to create measurable indicators for partnerships to be able to assess progress and effectiveness against specific dimensions for different research collaborations outside of the clinical trials setting.…”
Section: Lessons Learnt As Part Of This Process and Recommendations F...mentioning
confidence: 99%
“…Barriers to conducting research in LMICs include a shortage of financial and human capacity, difficulties navigating ethical and regulatory systems, limited preexisting research infrastructure, and competing demands on the part of healthcare systems ( 15 ). To overcome these barriers, potentially helpful actions include increasing the diversity of editorial boards ( 16 ); facilitating international collaboration within and across trials using harmonized protocols or platform, basket, and umbrella trial structures ( 17 ); ensuring equitable collaboration between HIC and LMIC researchers ( 18 ); integrating clinical trials with robust data collection and reporting systems ( 3 ); and empowering clinical research networks in resource-limited settings in the global south.…”
mentioning
confidence: 99%